Alcuni aspetti della trasposizione di un testo letterario in linguaggio cinematografico - Kováč-Petrovský, Dušan (Verbum – Analecta Neolatina, 2012)
The paper discusses some aspects of the transposition of literary texts into film language. This issue is illustrated through Tornatore’s film adaptation of Baricco’s text Novecento, which was shown in cinemas all over the world under the title La leggenda del pianista sull’oceano. The focus of the paper is on the reality of the viewers’ experience in contraposition with the artistic reality of the literary story and its film adaptation. The paper also discusses the relationship between the genre of the film and that of the literary piece as well as their potential to formulate artistic reality in time and space as defined by the literary artwork itself.